Serum Ampuh Penghilang Jerawat dan Memperbaiki Kulit yang Rusak Akibat Sinar Matahari dengan Menggunakan Bahan Alami Centella Asiatica - Mira Octaviani Malik; Syahdan Firdaus; Diajeng Lupitasari (Jurnal Ilmiah Wahana Pendidikan, 2022)
Currently, there are many topical anti-acne drugs circulating in the form of gels and creams, but there are still few topical anti-acne that contain herbs, as active ingredients or agents that have the potential to prevent and treat acne such as gotu kola (Centella asiatica (L.) Urb) with its anti-bacterial properties. Objective: To develop a stable gotu kola gel formulation. Method: Testing gotu kola formulation according to the evaluation requirements with a gel base concentration of 7%, 8%, 9%, then the evaluation includes testing of organoleptic, pH, and viscosity. The formula was added with gotu kola herb extract at a concentration of 2.5% and 5%. The formula evaluation tests carried out included observations of homogeneity, tests of acidity, viscosity and spreadability of the preparation. Results: The average pH of the preparation was 6.66. Formula 1 and Formula 2 there is a slight difference in viscosity. Formula 1 and Formula 2 show homogeneity and dispersion that have met the requirements. Conclusion: For 14 days, testing Formula 2 with an extract concentration of 5% was more stable than Formula 1 with an extract concentration of 2.5%.